2007
DOI: 10.1016/j.evalprogplan.2007.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Conflict of interest in the evaluation and dissemination of “model” school-based drug and violence prevention programs

Abstract: Conflict of interest refers to a set of conditions in which professional judgment concerning the validity of research might be influenced by a secondary competing interest. The competing interest that has received most attention in the literature addressing the prevalence and effects of such conflicts on the practice of empirical research has been that of financial relationships between investigators and research sponsors. The potential for conflicts of interest to arise in the evaluation of drug prevention pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 38 publications
0
29
0
1
Order By: Relevance
“…As a result, best practice lists create a strong incentive to achieve inclusion on those lists, and there is little doubt that some researchers actively lobby for inclusion of their products in those lists. Gorman (2006) identifies ideological conflict of interest as a second threat to prevention research. It arises in situations in which researchers hold strong normative views about core issues in their area of research.…”
Section: Conflict Of Interestmentioning
confidence: 98%
See 3 more Smart Citations
“…As a result, best practice lists create a strong incentive to achieve inclusion on those lists, and there is little doubt that some researchers actively lobby for inclusion of their products in those lists. Gorman (2006) identifies ideological conflict of interest as a second threat to prevention research. It arises in situations in which researchers hold strong normative views about core issues in their area of research.…”
Section: Conflict Of Interestmentioning
confidence: 98%
“…Petrosino and Soydan (2005) report that, in 56% of 281 studies included in their meta-analysis, the evaluation team included staff who also delivered the program. In a review of best-practice drug-prevention programs comprised in the National Registry of Effective and Promising Programs (NREPP), Gorman and Conde (2007) found that 78% of 246 evaluation studies included the program developer as one of the study authors and that only 11% of the evaluations could be regarded as completely independent.…”
Section: Conflict Of Interestmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on these studies the programs were placed on the Department of Education' s list of evidence-based model programs. The push to be included on evidence-based recommendation lists has intensified conflicts of interest because the designation is marketable (Gorman, 2006).…”
Section: Sponsorship Of the Study Terms Of The Contract Financial Tiementioning
confidence: 99%